USING OF PORTLAND CEMENT FOR THE SOIL STABILIZATION IN THE BUKIT RAWI VILLAGE, SUBDISTRICT CENTRAL KAHAYAN PULANG PISAU REGENCY - Ade Priawan; Lola Cassiophea (Jurusan Pendidikan Teknologi Dan Kejuruan, 2017)
The soil stabilization was an attempt to change or improve the engineering properties of soil in order to qualifycertain technical necessary. The engineering properties of soil which supports the carrying capacity were thatstrong value of the soil bearing (CBR) and free compressive strength (UCS). The soil of Bukit Rawi village, CentralKahayan subdistrict Pulang Pisau regency, as mentioned in the earlier study had a low ground bearing capacity.The problems of this is because of condition of fine soil grains being dominant and easily influenced by waterwhich has lead directly to its strong values of soil bearing (CBR) of the existing soil. For that, soil stabilizationwill be performed using portland cement. It is expected to improve the strong value of the soil bearing (CBR)and free compressive strength (UCS). In this study, the portland cement of Gresik brand is used as an additiveingredient of soil stabilization, which is applied in this study were 0%, 5%, 10%, 15%, 20%, 25% and 30%. Thetest was consisting of the physical soil properties which were bleded for testing moisture content, density,grained size distribution, the limits of atterberg, compaction, strong bearing capacity (CBR), and strenght freepress (UCS). Those were done during on a one day in laboratory of the Building Technical Education and StudyProgram The Faculty of Teacher Training and Education at under The University of Palangka Raya. The resultsshowed that the highest soil stabilization was on portland cement mix to 25% by 35.00%, with the strengthsupport of land value (CBR) increased by 28.75% from the original 6.25%, while the value of the compressivestrength of the free (UCS) on 20% of portland cement mixture of 1,200 kg/cm2 to free the compressive strength(UCS) fell by 0.360 kg/cm2, from its original condition 0.840 kg/cm2. Strenght value of soil bearing (CBR) wasoptimum mixture of portland cement with land of 35.00% by Bowles (1992) in Hardiyatmo (2012) optimommixture of 25% that this land including the strength support of land (CBR) 20% - 50% is recommened to be usedas subbase layer or subgrade, with the good results.